(untitled) (Research, Society and Development, 2025)
Introduction: Neurofibroma is a benign tumor of Schwann cell origin, with rare occurrence in the oral cavity, especially in the floor of the tongue. Its identification is important due to its similarities with other submucosal lesions and potential functional impairment. This article aims to present a case study of Neurofibroma in the floor of the tongue. Materials and Methods: This is a case study based on the analysis of medical records, clinical and histopathological examinations. Data were collected at the Oral and Maxillofacial Surgery and Traumatology outpatient clinic of the Sorocaba Hospital Complex, with approval from the Ethics Committee and informed consent from the patient. Results: A 51-year-old female patient presented with a bilateral lesion on the floor of the tongue, measuring approximately 5 cm, fibrous and pedunculated. Incisional biopsy confirmed the diagnosis of neurofibroma. Complete surgical excision was successfully performed, with no recurrence after six months of postoperative follow-up. Discussion: Despite the rarity of neurofibroma on the floor of the tongue, its inclusion in the differential diagnosis is essential. Confirmation by histopathology and immunohistochemistry (positive S-100 protein) is indispensable. Surgical excision represents the treatment of choice, with low recurrence rates and good functional recovery. Conclusion: Early diagnosis and appropriate surgical approach are essential for the control of lingual neurofibroma. The case reinforces the importance of clinical suspicion and multidisciplinary follow-up in the management of these rare lesions.